The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species - Smit, Harry (Zootaxa, 2019)
Two new species of the water mite genus Aspidiobates are described from Queensland, Australia, i.e. A. imperfectus n. sp. and A. neogeometricus n. sp. Many new records are given for eastern and south-eastern Australia. Finally, a key is provided for all Australian Aspidiobates species.